Pemahaman Siswa Sekolah Menengah Atas tentang Konsep Fungsi Invers (Jurnal Ilmiah Soulmath : Jurnal Edukasi Pendidikan Matematika, 2024)
Abstract Mathematical understanding is a person's capacity to recognize mathematical information and how this information is used as a strategy for solving an existing problem to achieve ease in obtaining the truth. However, students are still found who lack an understanding of inverse functions. This is very unfortunate, even though the inverse function is one of the materials that students must understand. This research aims to analyze students' mathematical understanding of inverse function material. This type of research is descriptive qualitative. The research subjects were 28 class XI students at one of Banda Aceh's high schools. Data collection used two instruments, namely a mathematical understanding test, and an interview guide. The triangulation used is time triangulation. The indicators tested on the test subjects were 1) restating the definition of the inverse function; 2) identifying functions that have an inverse and do not have an inverse; 3) showing examples and non-examples of functions that have an inverse; and 4) apply procedures and algorithms in solving inverse function problems. Based on the results of the analysis, show that a small number of students fulfill all the indicators of understanding in solving inverse function questions. Most students can apply the procedure but are unable to relate the answer to the concept of inverse functions. Keywords: Inverse functions; Comprehension indicators; Mathematical understanding. Abstrak Pemahaman matematis adalah kapasitas seseorang untuk mengenali informasi matematika dan bagaimana informasi tersebut digunakan sebagai strategi penyelesaian suatu permasalahan yang ada sehingga tercapainya kemudahan dalam memperoleh kebenaran. Namun faktanya masih ditemukan siswa yang kurang memiliki pemahaman fungsi invers. Hal ini sangat disayangkan, padahal fungsi invers merupakan salah satu materi yang harus dipahami oleh siswa. Penelitian ini bertujuan untuk menganalisis bagaimana pemahaman matematis siswa pada materi fungsi invers. Jenis penelitian ini adalah deskriptif kualitatif. subjek penelitian yaitu 28 siswa kelas XI di salah satu SMA Banda Aceh. Pengumpulan data menggunakan dua instrument yaitu tes pemahaman matematis dan panduan wawancara. Triangulasi yang digunakan adalah triangulasi waktu. Indikator yang diuji kepada subjek tes yaitu 1) menyatakan ulang definisi fungsi invers; 2) mengidentifikasikan fungsi yang memiliki invers dan tidak memiliki invers; 3) menunjukkan contoh dan non-contoh fungsi yang memiliki invers; dan 4) menerapkan prosedur dan algoritma dalam menyelesaikan soal fungsi invers. Berdasarkan hasil analisis menunjukkan sebagian kecil siswa memenuhi keseluruhan indikator pemahaman dalam menyelesaikan soal fungsi invers. Sebagian besar siswa mampu menerapkan prosedur namun tidak mampu mengaitkan jawaban dengan konsep dari fungsi invers. Kata Kunci: Fungsi invers; Indikator Pemahaman; Pemahaman Matematis.